GDM-5: Region specific high yielding and high oil content variety of Indian mustard (Brassica juncea L. Czern and Coss.) suitable for rainfed ecosystem: GDM-5: REGION SPECIFIC VARIETY OF INDIAN MUSTARD SUITABLE FOR RAINFED ECOSYSTEM - K P PRAJAPATI; J R PATEL; B K PATEL; S K SHAH; A L JAT; G P GANGWAR; A G DESAI (Journal of Oilseeds Research, 2019)
Indian mustard (Brassica juncea L. Czern & Coss.) variety GDM-5 (Gujarat Dantiwada Mustard 5) was developed by pedigree method of breeding from a cross between BIO 129-97 and NDR 9503 at Castor-Mustard ResearchStation, S. D. Agricultural University, Sardarkrushinagar, Gujarat. GDM-5 was evaluated in IVTand AVT Trials (rainfed) along with national check Kranti and zonal checks viz., Geeta, RB-50 and RGN-48 at five different locations during rabi 2011-12 to 2013-14. The genotype GDM-5 exhibited wider adaptability and consistent superiority for seed and oil yield in rainfed condition of Zone II as compared to the check varieties during the three year of testing. On the basis of weighted mean performance, GDM-5 gave 2213 kg/ha yield, which was higher than national check Kranti (1758 kg/ha) and zonal checks viz., Geeta (1238 kg/ha), RB-50 (1808 kg/ha) and RGN-48 (2013 kg/ha). GDM-5 with 40.50 per cent oil in its seed, gave on an average 897 kg/ha oil yield, which was higher than Kranti (by 24.6 %), Geeta (by 81.2 %), RB-50 (by 23.7 %) and RGN-48 (by 6.8 %). The genotype GDM-5 with medium tall growth habit has an inbuilt capacity for tolerance to lodging and shattering. It was found tolerant to biotic stresses like mustard aphid (under natural conditions), Sclerotinia stem rot, white rust and alternaria blight. On the basis of consistent superior performance, GDM-5 has been released in 2015 for general cultivation in rainfed area of Zone II including Punjab, Haryana, Delhi, Northern Rajasthan and Jammu states.